Служителі в домогосподарствах мешканців Полтави в 60-70-х роках XVIII ст. - Безсмертна, Ю. (Краєзнавство, 2019)
Стаття присвячена аналізу домогосподарств м. Полтави, у складі яких Генеральний опис
Лівобережної України 1765–1769 рр. зафіксував проживання «служителів». На основі перепису
підраховано кількість дворів, підварків та бездвірних хат, господарі яких наймали помічників по
господарству. Також обчислено кількість слуг у домогосподарствах різного типу власності. Особливої уваги заслуговує питання про місце проживання слуг у дворі, адже досить часто поряд із чисельною родиною господаря мешкала також й значна кількість служителів. Тож автор спробував проаналізувати, чи залежить чисельність слуг у господарстві від наявності «людських» чи їх відсутності. The article is devoted to the analysis of households in Poltava, in which the General description of
the Left Bank of Ukraine in 1765-1769 recorded the residence of servants. Despite the recent popularity
of urban studies, some aspects of the life of a large regimental center, such as the functioning of a large
layer of domestic staff among middle-class households, were only a matter of interest to some researchers.
But this is not enough for a clear understanding of the place of domestic service in the early life of a modern
city. It is necessary to answer the question about the prevalence of services, the number of employees
employed in different types of households, the place of employees in the house, and this is far from a complete
list.
The main source from which it was possible to make the appropriate calculations was a census book of the
city of Poltava, created in 1765-1766 during the description of Rumyantsev. The document was published in
2012, which greatly simplifies access to all historical information. On the basis of the census, the number of
different types of households whose owners hired domestic servants were counted. The number of employees
in households of owners, tenants, relatives, etc. is also calculated. Particular attention deserves a question
about the place of residence of servants in the yard, because often with the numerical family of the host, there
was a significant staff of servants. Given the large number of people living together and small-sized buildings,
one can assume that some employees had their own carbon fiber, where they worked, or in utility rooms. So the
author tried to analyze whether the number of employees in the house depends on the availability of rooms for
servants or their absence.